2020
DOI: 10.1016/j.hrthm.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sleep apnea and association with atrial fibrillation in an unselected pacemaker population: Results of the observational RESPIRE study

Abstract: BACKGROUND Patients with atrial fibrillation (AF) often have sleep apnea (SA), but diagnosis of SA with polysomnography is costly. SA monitoring is a pacemaker feature that measures respiratory disturbance index, the sum of abnormal respiratory events divided by sleep duration. OBJECTIVE The purpose of this study was to evaluate the incidence and severity of SA and its association with AF in an unselected population fitted with pacemakers. METHODS RESPIRE (REgistry of Sleep APnea monItoring and Atrial Fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…OSA has been identified as an independent risk factor for a large number of diseases. Among these, acute coronary syndrome (ACS) [ 111 ], atrial fibrillation (AF) [ 112 , 113 ], stroke [ 114 ], and venous thromboembolism (VTE) [ 115 , 116 ] are prominently represented.…”
Section: Potential Therapiesmentioning
confidence: 99%
“…OSA has been identified as an independent risk factor for a large number of diseases. Among these, acute coronary syndrome (ACS) [ 111 ], atrial fibrillation (AF) [ 112 , 113 ], stroke [ 114 ], and venous thromboembolism (VTE) [ 115 , 116 ] are prominently represented.…”
Section: Potential Therapiesmentioning
confidence: 99%
“…SA has a prevalence of about 60% in patients implanted with pacemakers according to conventional indications 11 . Recently, automated pacemaker algorithms have been developed to calculate a Respiratory Disturbance Index (RDI) that well correlates with the results of standard polysomnography, 12,13 and that showed a good performance in identifying patients at higher risk of new‐onset AF over the mid‐term 14,15 . The availability of these algorithms offers the opportunity to monitor sleep‐disordered breathing in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Among the study participants, 21.4% had severe SDB with an AHI >30 events/h. In turn, Marti-Almor et al [33], in a REgistry of Sleep APnea monItoring and Atrial Fibrillation in pacemakeR patients (RESPIRE study), found severe OSA, defined as a respiratory disturbance index of ≥20, in 31.1% of patients with PM capable of detecting SDB. The high sensitivity and specificity of PM with transthoracic impedance sensor in the diagnosis of severe SDB were confirmed by Defaye et al [34] and may improve the initial diagnosis of OSA in the group of patients with permanent cardiac pacing.…”
Section: Discussionmentioning
confidence: 97%
“…The coexistence of sinus bradycardia during sleep and paroxysmal AF (tachycardia-bradycardia syndrome, T-B syndrome) occurred in nine patients (4.3%). It is worth noting that SDB is a significant and reversible risk factor of new-onset AF, T-B syndrome, and AF recurrence despite adequate pharmacological treatment or with the use of ablation techniques [2,20,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%